2003
DOI: 10.1002/etc.5620220118
|View full text |Cite
|
Sign up to set email alerts
|

Tributyltin causes masculinization in fish

Abstract: We examined the effect of tributyltin (TBT) on the sex differentiation process in genetically female Japanese flounder (Paralichthys olivaceus). The fish were fed an artificial diet containing tributyltin oxide (TBTO) at concentrations of 0.1 and 1.0 microg/g diet from 35 to 100 d after hatching, which includes the sex differentiation period. The ratio of sex-reversed males significantly increased to 25.7% of the flounder fed the 0.1 microg/g diet and to 31.1% of those fed the 1.0 microg/g diet compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 161 publications
(37 citation statements)
references
References 33 publications
3
30
0
4
Order By: Relevance
“…Despite this, TBT has also induced hermaphroditism in M. rosenbergii . Supportively, Shimasaki et al [63] found that the TBT has potentially induced masculinization to the extent of complete sex reversal in the genetically female Japanese flounder Paralichthys olivaceus .…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, TBT has also induced hermaphroditism in M. rosenbergii . Supportively, Shimasaki et al [63] found that the TBT has potentially induced masculinization to the extent of complete sex reversal in the genetically female Japanese flounder Paralichthys olivaceus .…”
Section: Discussionmentioning
confidence: 99%
“…Hardly a decade after organotins were introduced, the first reports of imposex in snails surfaced 29-30 and subsequent studies identified TBT as the causative agent 31-33 . Given that snails lack most vertebrate orthologs of sex steroid receptors (e.g., androgen and progesterone receptors) 34 , this result did not interest vertebrate developmental biologists until 2003 when TBT was shown to masculinize female fish 35-36 . The mechanism proposed was that TBT inhibited aromatase action, thereby preventing the biosynthesis of estradiol from testosterone 37-38 .…”
Section: A Brief History Of Obesogensmentioning
confidence: 99%
“…Effects of TBT have been investigated in several aquatic organisms, including algae [5] and crustaceans [6]. Champ [7] reported that TBT inhibits growth, reproduction [8,9] and sexual differentiation in fishes [10]. In our previous study, we documented the inhibition of organogenesis as well as embryonic development in M. rosenbergii due to TBT toxicity [11].…”
Section: Introductionmentioning
confidence: 99%